Peran Kegiatan Ekstrakurikuler Palang Merah Remaja dalam Membentuk Keterampilan Peserta Didik - Muhammad Arif; Silvana Bayu; Nur Arifa Hasanah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
This research aims to determine the role of Red Cross Youth extracurricular activities in shaping students' skills. This type of research is research and development with a qualitative method which uses three main techniques, namely interviews, observation and documentation studies. Based on the results of interviews conducted, it can be concluded that there are several extracurricular activities of the Youth Red Cross (PMR) which play a role in forming students, including First Aid Training, Humanitarian Activities, Community Service, Management Training and Leadership Training.